Necesidad de reformar el artículo 246 del código orgánico integral penal ecuatoriano regulando la aplicación de sanciones penales ambientales en el marco de los principios de prevención y de proporcionalidad - Cuenca Aguilar, Edwin Michael (2016)
This thesis entitled: "NEED TO AMEND ARTICLE 246 OF THE CODE OF CRIMINAL INTEGRAL ECUADORIAN REGULATING THE APPLICATION OF ENVIRONMENTAL CRIMINAL PENALTIES UNDER THE PRINCIPLES OF PREVENTION AND PROPORTIONALITY", in the context of my subject of study itself, palpate the need for a compilation and analysis of legal doctrine, jurisprudence and legal regulations in our country, so that once the analysis of the problems regarding sanctions and penalties for those who damage the environment, and legal issues made imperatively important for its consequence in the social field of law, scientific and academic hierarchy, through which I allowed to expand and feed back the referential framework for addressing this issue with sufficient evidence to the social, political, economic , family and child that is our Ecuadorian society. This work was developed through a methodology with application of methods and techniques that served as tools for collecting and processing the information that helped to get to conclusions, recommendations and drafting of legal reform to the Organic Code Integral Criminal.